NO003 The quality of care questionnaire—development of a valid measure for persons with inflammatory bowel disease. (16th January 2018) - Pihl Lesnovska, K; Börjeson, S; Hollman Frisman, G; Hjortswang, H; Wenemark, M
Abstract: Background: Inflammatory bowel disease (IBD) comprises ulcerative colitis and Crohn's disease. Lifelong contact with health care services is often needed when living with a chronic condition such as IBD. 1, 2 Quality of care (QoC)can be assessed in numerous ways, such as measuring the structure, the process, and the outcomes of health care. 3, 4 As a short, respondent focused questionnaire was lacking, there was a need to develop a questionnaire evaluating QoC from the perspective of persons with IBD. Therefore, we initiated the current study. The aim of the present study was to develop a questionnaire measuring quality of care in persons with IBD. Methods: The development of the questionnaire The Quality of Care scale-IBD (QoC-IBD) was based on a literature review of studies measuring QoC, and the results of two qualitative studies aiming to identify the knowledge need and perception of health care among persons with IBD. The first version of the questionnaire consisted of 24 questions. Results: The development phase resulted in a questionnaire consisting of 21 questions in the dimensions trust and respect, decision-making, information, continuity, one question about access to care, including six subqueries, and finally one question about satisfaction with health care as a whole. Six hundred persons with a confirmed diagnosis of IBD, who had received care at the IBD clinic at a university hospital in south-east Sweden between September 2014 and September 2015, were invited to participate in the evaluation of the questionnaire. In all, 294 patients (49%) returned the questionnaires. Test–retest reliability was determined between the two measurements in 83 patients. The question non-response of the QoC-IBD was between 0.7- 3.9%. Confirmatory factor analysis was performed to determine the construct validity of the QoC-IBD. The maximum likelihood method with varimax rotation was used. Only factors with an eigen value greater than 1 were extracted. Each question was affiliated to the factor on which it exerted the greatest loading. Factor loadings over 0.4 were deemed as significant. Four factors were identified, explaining 61% of the variance. Test–retest reliability for the QoC-IBD was analysed with Spearman's correlation. Internal consistency reliability tested with Cronbach's α for the QoC-IBD was α = 0.811. Cronbach's α for the importance questions in the QUOTE-IBD was α = 0.908. Conclusions: The questionnaire can be considered as feasible. This is an important step in the direction of evaluating health care in a person-centred way, as health care organisations strive for a person-centred approach. Further testing is suggested to assess if the QoC-IBD can be used to evaluate care and areas of improvement in health care for persons living with IBD. References: 1. O'Connor M, Bager P, Duncan J, et al . N-ECCO Consensus statements on the European nursing roles in caring for patients with Crohn's disease or ulcerative colitis. J Crohns Colitis 2013;7:744-64. 2. Kappelman MD, Palmer L, Boyle BM, et al . Quality of care in inflammatory bowel disease: a review and discussion. Inflamm Bowel Dis 2010;16:125-33. 3. van der Eijk I, Stockbrugger R, Russel M. Influences of quality of care on quality of life in inflammatory bowel disease (IBD): literature review and studies planned. Eur J Int Med 2000;11:228-34. 4. Donabedian A. Evaluating the quality of medical care. Milbank Quart, 2005;83:691–729.